Mechanical joining without auxiliary element by cold formed pins for multi-material-systems - Kraus, M.; Frey, P.; Kleffel, T.; Drummer, D.; Merklein, M. (AIP Conference Proceedings)

Numerical analysis of the robustness of clinching process considering the pre-forming of the parts - Bielak, Christian Roman; Böhnke, Max; Beck, Robert; Bobbert, Mathias; Meschut, Gerson (Journal of Advanced Joining Processes.)
Keywords: Clinching; process simulation; FEM; pre-straining; sensitivity analysis

A New Approach for the Evaluation of Component and Joint Loads Based on Load Path Analysis - Steinfelder, C.; Brosius, A. (Lecture Notes in Production Engineering)

Characterization and Numerical Modelling of Through-Thickness Metallic-Pin-Reinforced Fibre/Thermoplastic Composites under Bending Loading - Böhm, H.; Zhang, H.; Gröger, B.; Hornig, A.; Gude, M. (Journal of Composites Science)

Investigation of Clinched Joints – A Finite Element Simulation of a Non-destructive Approach - Sadeghian, B.; Guilleaume, C.; Lafarge, R.; Brosius, A. (Lecture Notes in Production Engineering)

Untersuchungen zum Einfluss von Geometrieparametern bei artgleichen Al-Clinchverbindungen auf das Ermüdungsverhalten im Bereich hoher bis sehr hoher Lastspielzahlen - Ewenz, L.; Schettler, S.; Zeuner, A. T.; Zimmermann, M. (Tagung Werkstoffprüfung 2020. Werkstoffe und Bauteile auf dem Prüfstand. Prüftechnik - Kennwertermit)

Influence of Nozzle Shape on Near-Surface Segregation Formation During Twin-Roll Casting of Aluminum Strips - Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Light Metals 2020)

Experimental and Numerical Studies on the Deformation of a Flexible Wire in an Injection Moulding Process - Köhler, D.; Gröger, B.; Kupfer, R.; Hornig, A.; Gude, M. (Procedia Manufacturing)

Potentiale datengestützter Methoden zur Gestaltung und Optimierung mechanischer Fügeverbindungen - Zirngibl, C.; Schleich, B.; Wartzack, S. (Proceedings of the 31st Symposium Design for X (DFX2020))

Clinching in in-situ CT—A numerical study on suitable tool materials - Köhler, D.; Kupfer, R.; Gude, M. (Journal of Advanced Joining Processes)

Potential of Joining Dissimilar Materials by Cold Formed Pin-Structures - Kraus, M.; Merklein, M. (Journal of Materials Processing Technology)

Development of a numerical method for analyzing the robustness of clinching in versatile process chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson

Test Method for Friction Characterization of Rivets - Wituschek, S.; Kuball, C. M.; Merklein, M.; Lechner, M. (Defect and Diffusion Forum)

Development of a special specimen geometry for the experimental determination of fracture mechanical parameters of clinchable metal sheets - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter

Experimental and numerical preliminary investigations of the base material and preformed components regarding fatigue crack growth in joined structures - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter

Investigation of influencing parameters on the joint formation of the self-piercing riveting process - Kappe, Fabian; Wituschek, Simon; Lechner, Michael; Bobbert, Mathias; Meschut, Gerson; Merklein, Marion

Probability Distribution of Joint Point Loadings in Car Body Structures under Global Bending and Torsion - Martin, Sven; Camberg, Alan A.; Tröster, Thomas (Procedia Manufacturing)

Joining with Versatile Friction-Spun Joint Connectors - Rostek, Tim; Wiens, Eugen; Homberg, Werner (Procedia Manufacturing)

Clinching in in-situ CT—A numerical study on suitable tool materials - Köhler, Daniel; Kupfer, Robert; Gude, Maik (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Inverse parameter identification of an anisotropic plasticity model for sheet metal - Friedlein, J.; Wituschek, S.; Lechner, M.; Mergheim, J.; Steinmann, P. (IOP Conference Series: Materials Science and Engineering)
The increasing economic and ecological demands on the mobility sector require efforts to reduce resource consumption in both the production and utilization phases. The use of lightweight construction technologies can save material and increase energy efficiency during operation. Multi-material systems consisting of different materials and geometries are used to achieve weight reduction. Since conventional joining processes reach their limits in the connection of these components, new methods and technologies are necessary in order to be able to react versatilely to varying process and disturbance variables. For fundamental investigations of new possibilities in joining technology, numerical investigations are helpful to identify process parameters. To generate valid results, robust and efficient material models are developed which are adapted to the requirements of versatile joining technologies, for instance to the high plastic strains associated with self-piercing riveting. To describe the inherent strain-induced plastic orthotropy of sheet metal an anisotropic Hill-plasticity model is formulated. Tensile tests for different sheet orientations are conducted both experimentally and numerically to adjust the anisotropic material parameters by inverse parameter identification for aluminium EN AW-6014 and steel HCT590X. Then, the layer compression test is used to validate the model and the previously identified parameters.

Energy direction in ultrasonic impregnation of continuous fiber-reinforced thermoplastics - Popp, J.; Wolf, M.; Mattner, T.; Drummer, D. (Journal of Composites Science)
As a new and innovative processing method for fabrication for fiber-reinforced thermoplastic composites (CFRTs), the feasibility of ultrasonic welding technology was proven in several studies. This method offers potential for the direct manufacturing of CFRT–metal structures via embedded pin structures. Despite the previous studies, a deeper understanding of the process of energy input and whether fibers work as energy directors and consequently can, in combination with chosen processing parameters, influence the consolidation quality of the CFRTs, is still unknown. Consequently, the aim of this work is to establish a deeper process understanding of the ultrasonic direct impregnation of fiber-reinforced thermoplastics with an emphasis on the fiber’s function as energy directors. Based on the generated insights, a better assessment of the feasibility of direct, hybrid part manufacturing is possible. The produced samples were primarily evaluated by optical and mechanical test methods. It is demonstrated that with higher welding time and amplitude, a better consolidation quality can be achieved and that independent of the process parameters chosen in this study, no significant fiber breakage occurs. This is interpreted as a sign of a gentle impregnation process. Furthermore, based on the examination of single roving and 5-layer set-ups, it is shown that the glass fibers function as energy directors and can influence the transformation of sonic energy into thermal energy. In comparison to industrially available CFRT material, the mechanical properties are weaker, but materials and processes offer potential for significant improvement. Based on these findings, proposals for a direct impregnation and joining process are made.

Influence of the production process on the binding mechanism of clinched aluminum steel mixed compounds - Kalich, J.; Füssel, U. (Journal of Manufacturing and Materials Processing)
The multi-material design and the adaptability of a modern process chain require joining connections with specifically adjustable mechanical, thermal, chemical, or electrical properties. Previous considerations primarily focused on the mechanical properties. The multitude of possible combinations of requirements, materials, and component- and joining-geometry makes an empirical determination of these joining properties for the clinching process impossible. Based on the established and empirical procedure, there is currently no model that takes into account all questions of joinability—i.e., the materials (suitability for joining), design (security of joining), and production (joining possibility)—that allows a calculation of the properties that can be achieved. It is therefore necessary to describe the physical properties of the joint as a function of the three binding mechanisms—form closure, force closure, and material closure—in relation to the application. This approach illustrates the relationships along the causal chain “joint requirement-binding mechanism-joining parameters” and improves the adaptability of the mechanical joining technology. Geometrical properties of clinch connections of the combination of aluminum and steel are compared in a metallographic cross-section. The mechanical stress state of the rotationally symmetrical clinch points is qualified with a torsion test and by measuring the electrical resistance in the base material, in the clinch joint, and during the production cycle (after clinching, before precipitation hardening and after precipitation hardening).

Stochastic local FEM for computational homogenization of heterogeneous materials exhibiting large plastic deformations - Pivovarov, D.; Mergheim, J.; Willner, K.; Steinmann, P. (Computational Mechanics)
Computational homogenization is a powerful tool allowing to obtain homogenized properties of materials on the macroscale from simulations of the underlying microstructure. The response of the microstructure is, however, strongly affected by variations in the microstructure geometry. In particular, we consider heterogeneous materials with randomly distributed non-overlapping inclusions, which radii are also random. In this work we extend the earlier proposed non-deterministic computational homogenization framework to plastic materials, thereby increasing the model versatility and overall realism. We apply novel soft periodic boundary conditions and estimate their effect in case of non-periodic material microstructures. We study macroscopic plasticity signatures like the macroscopic von-Mises stress and make useful conclusions for further constitutive modeling. Simulations demonstrate the effect of the novel boundary conditions, which significantly differ from the standard periodic boundary conditions, and the large influence of parameter variations and hence the importance of the stochastic modeling.

Anisotropic plasticity‐damage material model for sheet metal — Regularised single surface formulation - Friedlein, J.; Mergheim, J.; Steinmann, P. (PAMM)
Sheet metal forming as well as mechanical joining demand increasingly accurate and efficient material modelling to capture large deformations, the inherent sheet orthotropy and even process-induced damage, which is expected to be influential. To account for large strains the additive logarithmic strain space is utilised that enables a straightforward incorporation of plastic anisotropy, herein modelled by a Hill48 yield function. A gradient-enhancement is used to equip the ductile damage model with an internal length scale curing the damage-induced localisation. An affine combination of the local and non-local softening variable is derived enabling a more efficient single surface formulation for the regularised plasticity-damage material model.

Further development of a numerical method for analyzing the load capacity of clinched joints in versatile process chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson

Data-driven analysis of cold-formed pin structure characteristics in the context of versatile joining processes - Römisch, D.; Zirngibl, C.; Schleich, B.; Wartzack, S.; Merklein, M. (IOP Conference Series: Materials Science and Engineering)
Due to increasingly strict emission targets and regulatory requirements, especially for companies in the transport industry, the demand for multi-material-systems is continuously rising in order to lower energy consumption. In this context, mechanical joining processes offer an environmentally friendly and flexible alternative to established joining methods, especially in the field of lightweight design. For example, cold-formed cylindrical pin structures show high potentials in joining multi-material-systems without auxiliary elements. The pin structures are joined either by pressing them directly into the joining partner or by caulking with a pre-punched part. However, to evaluate the strength of the joint and to ensure the joining reliability for versatile processes, such as changing joining partners or batch variations, engineering designers currently have only limited design principles available compared to thermal joining processes. Consequently, the design of an optimal pin joint requires cost- and time-intensive experimental investigations and adjustments to design or process parameters. As a solution, data-driven methods offer procedures for structuring data and identifying dependencies between varying process parameters and resulting pin structure characteristics. Motivated by this, the paper presents an approach for the data-driven analysis of cold-formed pin structures and offers a deeper understanding of how versatile processes affect the pin characteristics. Therefore, the application of an intelligent design of experiment in combination with several machine learning methods enable the setup of a best-fitting meta-model. Resulting, the determination of a mathematical model provides the opportunity to accurately estimate the pin height considering only relevant geometrical and process parameters with a prediction quality of 95 %.

Numerical and experimental investigation of the transmission moment of clinching points - Steinfelder, C.; Kalich, J.; Brosius, A.; Füssel, U. (IOP Conference Series: Materials Science and Engineering)
In clinching, the combinations of requirements, materials, component dimensions and tools influence the resulting joint geometry and the resulting bonding mechanisms. These in turn affect the property profile of the joint. For example, it is possible to use different tools to flexibly adapt clinching points to the respective required load regime. Clinching points dimensioned in this way can be geometrically similar, but have different mechanical stress states, which leads to different properties in terms of load-bearing behavior. Within the scope of this work, the clinching process with different tools in optimal and compromise design and its effect on the force and form-closure component, is investigated in a torsion test of the clinched connection. Clinched steel sheets with two thicknesses and joining directions are analyzed. Virtual experiments are carried out using finite element analyses (FEA) of the joining process and are followed by a springback simulation. Subsequently, the surface pressure between the two joining partners in the clinching points is calculated on the basis of the results from the FEA and the transmittable moment of the connection, as an indicator for the force-closure component, is determined. Finally, the experimental and simulated data are compared and discussed.

Fiber Orientation Mechanism of Continuous Fiber Reinforced Thermoplastics Hybrid Parts Joined with Metallic Pins - Popp, J.; Kleffel, T.; Römisch, D.; Papke, T.; Merklein, M.; Drummer, D. (Applied Composite Materials)
Continuous Fiber Reinforced Thermoplastic (CFRT) hybrid parts offer interesting possibilities for lightweight application, which can exceed the capabilities of mono material metal or CFRT parts. In this case, the joining technology oftentimes is the limiting factor. This study investigates a joining operation with metal pin structures which are additively manufactured via powder bed fusion featuring different diameters and tip geometries, which are inserted into the locally infrared heated CFRT part. The resulting fiber rearrangement is assessed using transmitted light microscopy, confocal laser scanning microscopy as well as micro-computer-tomography. It could be shown that for all assessed pin variants a similar distinct fiber displacement can be seen and that the pin diameter has a significant effect on the resulting fiber orientation with smaller pin diameters being advantageous because of gentle fiber displacement and reduced undulation. The tip geometry has only minor effect on the fiber orientation. Especially in the X/Y plane no systematic influence of the tip geometry on the fiber displacement could be observed. Based on the gained insights a three-stage model of the fiber orientation processes is proposed.

Clinching of Thermoplastic Composites and Metals—A Comparison of Three Novel Joining Technologies - Gröger, B.; Troschitz, J.; Vorderbrüggen, J.; Vogel, C.; Kupfer, R.; Meschut, G.; Gude, M. (Materials)
Clinching continuous fibre reinforced thermoplastic composites and metals is challenging due to the low ductility of the composite material. Therefore, a number of novel clinching technologies has been developed specifically for these material combinations. A systematic overview of these advanced clinching methods is given in the present paper. With a focus on process design, three selected clinching methods suitable for different joining tasks are described in detail. The clinching processes including equipment and tools, observed process phenomena and the resultant material structure are compared. Process phenomena during joining are explained in general and compared using computed tomography and micrograph images for each process. In addition the load bearing behaviour and the corresponding failure mechanisms are investigated by means of single-lap shear tests. Finally, the new joining technologies are discussed regarding application relevant criteria.

Determination of the Interface Structural Resolution of an Industrial X-Ray Computed Tomograph Using a Spherical Specimen and a Gap Specimen Consisting of Gauge Blocks - Busch, M.; Hausotte, T. (Key Engineering Materials)
Industrial X-ray computed tomography (XCT) is a tool for non-destructive testing and a volumetric analysis method with the ability to measure dimensions and geometry inside a component without destroying it. However, XCT is a relatively young technology in the field of dimensional metrology and thus faces several challenges. The achievement of a high measurement resolution, which is re-quired to detect small geometrical features, depends on a variety of influencing factors. In this arti-cle, the interface structural resolution (ISR) as one of the key challenges will be investigated. The two-sphere standard called the hourglass standard allows the determination of the structural resolu-tion by evaluation of the surrounding area of an ideal point contact of two spheres after the CT re-construction in form of a neck-shaped transition. Close to the contact point of the two spheres two opposing surfaces exist. Their distances from each other increase as the distance from the contact point of the two spheres increase. The determination of the distances between the spheres’ surface allows a statement about the ISR. A new developed specimen or standard with a variable gap size consisting of calibrated parallel gauge blocks allows statements about the ISR, too. Because of the higher number of probing points of the gauge block standard the results of the determined ISR are more stable compared to the hourglass standard. This paper compares the results of the computed tomography measurements for the designed interface structural resolution standard with those of the hourglass standard.

Clinching in In-situ CT – Experimental Study on Suitable Tool Materials - Köhler, D.; Kupfer, R.; Troschitz, J.; Gude, M. (ESAFORM 2021)
In lightweight design, clinching is a cost-efficient solution as the joint is created through localized cold-forming of the joining parts. A clinch point’s quality is usually assessed using ex-situ destructive testing methods. These, however, are unable to detect phenomena immediately during the joining process. For instance, elastic deformations reverse and cracks close after unloading. In-situ methods such as the force-displacement evaluation are used to control a clinching process, though deviations in the clinch point geometry cannot be derived with this method. To overcome these limitations, the clinching process can be investigated using in-situ computed tomography (in-situ CT). However, a clinching tool made of steel would cause strong artefacts and a high attenuation in the CT measurement, reducing the significance of this method. Additionally, when joining parts of the same material, the sheet-sheet interface is hardly detectable. This work aims at identifying, firstly, tool materials that allow artefact-reduced CT measurements during clinching, and, secondly, radiopaque materials that can be applied between the joining parts to enhance the detectability of the sheet-sheet interface. Therefore, both CT-suitable tool materials and radiopaque materials are selected and experimentally investigated. In the clinching process, two aluminium sheets with radiopaque material in between are clinched in a single-step (rotationally symmetric joint without cut section). It is shown that e.g. silicon nitride is suited as tool material and a tin layer is suitable to enhance the detectability of the sheet-sheet interface.

In Situ Computed Tomography—Analysis of a Single-Lap Shear Test with Clinch Points - Köhler, D.; Kupfer, R.; Troschitz, J.; Gude, M. (Materials)
As lightweight design gains more and more attention, time and cost-efficient joining methods such as clinching are becoming more popular. A clinch point’s quality is usually determined by ex situ destructive analyses such as microsectioning. However, these methods do not yield the detection of phenomena occurring during loading such as elastic deformations and cracks that close after unloading. Alternatively, in situ computed tomography (in situ CT) can be used to investigate the loading process of clinch points. In this paper, a method for in situ CT analysis of a single-lap shear test with clinched metal sheets is presented at the example of a clinched joint with two 2 mm thick aluminum sheets. Furthermore, the potential of this method to validate numerical simulations is shown. Since the sheets’ surfaces are locally in contact with each other, the interface between both aluminum sheets and therefore the exact contour of the joining partners is difficult to identify in CT analyses. To compensate for this, the application of copper varnish between the sheets is investigated. The best in situ CT results are achieved with both sheets treated. It showed that with this treatment, in situ CT is suitable to properly observe the three-dimensional deformation behavior and to identify the failure modes.

Friction Characterisation for a Tumbling Self-Piercing Riveting Process - Wituschek, S.; Lechner, M. (Key Engineering Materials)
Due to increasing demands regarding ecological and economic specifications in vehicle design, the effort required for production is continuously increasing. One trend is the increased use of multi-material systems, which are characterised by the use of different materials such as high-strength steels or aluminium alloys. In addition to the varying mechanical properties of the components, an increased number of variants accompanied by different geometries is leading to increasing challenges on body construction. For the assembly and connection of the individual components, conventional joining methods reach their limitations. Therefore, new joining methods are necessary, which feature properties of versatility and can adapt to process and disturbance variables. One way of achieving tailored joints is to use a tumbling self-piercing riveting process. For the design of the process route, numerical investigations are necessary for which a characterisation of the friction properties is necessary. This paper therefore investigates the contact and friction conditions that occur in a tumbling self-piercing riveting process. The individual contacts between the process components are identified and based on this, suitable processes for the characterisation of the friction factors - and coefficients are selected and performed.

Joining with Friction Spun Joint Connectors – Manufacturing and Analysis - Wischer, Christian; Steinfelder, Christian; Homberg, Werner; Brosius, Alexander (IOP Conference Series: Materials Science and Engineering)
Nowadays, the production of modern lightweight structures, like a body in white structure requires a wide variety of mechanical joining processes. To fulfill the various demands, mechanical joining processes and joining elements (JE) are used. Very often, they are adapted to the application, which leads in turn to a numerous of different variants, high costs, and loss of the process chain versatility. To overcome this drawback, an innovative approach is the usage of individually produced and task-adapted JE, the so-called friction spun joint connectors (FSJC). These connectors can be modified in shape as well as in material properties. This flexibility offers high potential for lightweight design but also increases the necessary analytical effort regarding the forming process as well as the manufactured joint's properties. Therefore, a new analysis strategy based on the Finite-Element-Method (FEM) is proposed, which numerically determines the local load bearing capacity within a given joint in order to identify the critical regions for load transfer. The process of joining element manufacturing and the analysis strategy will be described in detail and optimization results of the joints are shown. Numerical results are discussed and possible recommendations for joint manufacturing are derived.

A contribution on versatile process chains: joining with adaptive joining elements, formed by friction spinning - Wischer, Christian; Homberg, Werner (Production Engineering)

Numerical and Experimental Fracture Mechanical Investigations of Clinchable Sheet Metals Made of HCT590X - Weiß, D.; Schramm, B.; Kullmer, G. (Key Engineering Materials)

Computed tomography investigation of the material structure in clinch joints in aluminium fibre-reinforced thermoplastic sheets - Gröger, B.; Köhler, D.; Vorderbrüggen, J.; Troschitz, J.; Kupfer, R.; Meschut, G.; Gude, M. (Production Engineering)

Holistic investigation chain for the experimental determination of fracture mechanical material parameters with special specimens - Weiß, D.; Schramm, B.; Kullmer, G. (Production Engineering)

Approach for the automated and data-based design of mechanical joints - Zirngibl, C.; Schleich, B.; Wartzack, S. (Proceedings of the Design Society)

Application of reinforcement learning for the optimization of clinch joint characteristics - Zirngibl, C.; Dworschak, F.; Schleich, B.; Wartzack, S. (Production Engineering)

Joining of CFRT-steel hybrid parts via hole-forming and subsequent pin caulking - Römisch, D.; Popp, J.; Drummer, D.; Merklein, M. (Production Engineering)

A New Non-destructive Testing Method Applied to Clinching - Lafarge, R.; Wolf, A.; Guilleaume, C.; Brosius, A. (Minerals, Metals and Materials Series)

Experimental study on joining by forming of hct590x + z and en-aw 6014 sheets using cold extruded pin structures - Römisch, D.; Kraus, M.; Merklein, M. (Journal of Manufacturing and Materials Processing)
Due to stricter emission targets in the mobility sector and the resulting trend towards lightweight construction in order to reduce weight and consequently emissions, multi-material systems that allow a material to be placed in the right quantity and in the right place are becoming increasingly important. One major challenge that is holding back the rapid and widespread use of multi-material systems is the lack of adequate joining processes that are suitable for joining dissimilar materials. Joining processes without auxiliary elements have the advantage of a reduced assembly effort and no additional added weight. Conventional joining processes without auxiliary elements, such as welding, clinching, or the use of adhesives, reach their limits due to different mechanical properties and chemical incompatibilities. A process with potential in the field of joining dissimilar materials is joining without an auxiliary element using pin structures. However, current pin manufacturing processes are mostly time-consuming or can only be integrated barely into existing industrial manufacturing processes due to their specific properties. For this reason, the present work investigates the production of single- and multi-pin structures from high-strength dual-phase steel HCT590X + Z (DP600, t0 = 1.5 mm) by cold extrusion directly out of the sheet metal. These structures are subsequently joined with an aluminium sheet (EN AW-6014-T4, t0 = 1.5 mm) by direct pin pressing. For a quantitative evaluation of the joint quality, tensile shear tests are carried out and the influence of different pin heights, pin number, and pin arrangements, as well as different joining strategies on the joint strength is experimentally evaluated. It is proven that a single pin structure with a diameter of 1.5 mm and an average height of 1.86 mm achieves a maximum tensile shear force of 1025 N. The results reveal that the formation of a form-fit during direct pin pressing is essential for the joint strength. By increasing the number of pins, a linear increase in force could be demonstrated, which is independent of the arrangement of the pin structures.

Investigation of Different Joining by Forming Strategies when Connecting Different Metals without Auxiliary Elements - Römisch, D.; Kraus, M.; Merklein, M. (Key Engineering Materials)
Lightweight constructions become more and more important, especially in the mobility sector. In this industry, the increasingly strict regulations regarding the emissions of carbon dioxide can be achieved to a certain extent by reducing the vehicle weight. Thus, multi-material systems are used. Conventional joining techniques reach their limits when joining different materials due to different thermal expansion, unequal stiffness or chemical incompatibilities. This is why additional joining elements or adhesives are used. These must be viewed critically regarding a lightweight and resource-efficient production, since they add weight or complicate the recycling process of these components. Consequently, there is a great and growing need for new versatile joining technologies in order to overcome these challenges and to be able to react to changing process parameters and boundary conditions. Joining without an auxiliary element using pin structures formed directly from the sheet metal plane is one approach to meet these challenges. These pin structures are then joined by direct pressing into the joining partner. This is possible with a variety of material combinations, but is advantageous with regard to continuous fibre-reinforced thermoplastic composites (CFRTP), as the fibres do not have to be cut when joining CFRTP using pin structures. In this paper, the formability of pin structures made of a dual-phase steel DP600 (HCT590X + Z) is investigated. The extruded pin structures are joined by direct pin pressing with an EN AW-6014 to form tensile shear specimens. Different joining strategies are investigated to compare their influence on the joint strength. The results have shown that it is feasible to form suitable pins from a DP600 dual-phase steel to produce reliable connections with an aluminium sheet joined by direct pin pressing.

Material characterisation methods for a tumbling self-piercing riveting process - Wituschek, S.; Lechner, M. (ESAFORM 2021)
The growing demands of resource-saving processes and products are leading to increasing importance of lightweight construction for the automotive industry. One approach is multi-material design, which uses high-strength steels and aluminium alloys in the production of vehicle bodies. Therefore, reliable processes for joining components with different mechanical properties and geometries are necessary. As conventional joining processes reach their limits, new versatile processes and methods are required which can adapt to different process conditions and disturbance variables. A widely used joining process to join different materials is self-piercing riveting as a joining by forming method, however it is characterised as inflexible to changing process conditions due to a linear process kinematic and rigid dies. An approach to extend the process limits is the application of a tumbling kinematic for the punch. Thus, an adapted tumbling strategy can be used to influence the joining process and to achieve a controlled material flow in order to manufacture tailored joints. For the fundamental investigation of the process, numerical investigations are necessary. In order to achieve high model quality a precise material modelling is crucial. Therefore, a characterisation of the materials HCT590X+Z and EN AW-6014 as typical materials of multi-material mixes and the rivet material 38B2 is performed. Due to the different stress conditions during tumbling self-piercing riveting suitable characterisation methods are selected and carried out.

A Method for Characterization of Geometric Deviations in Clinch Points with Computed Tomography and Transient Dynamic Analysis - Köhler, D.; Sadeghian, B.; Kupfer, R.; Troschitz, J.; Gude, M.; Brosius, A. (Key Engineering Materials)
When joining lightweight parts of various materials, clinching is a cost efficient solution. In a production line, the quality of a clinch point is primarily controlled by measurement of dimensions, which are accessible from outside. However, methods such as visual testing and measuring the bottom thickness as well as the outer diameter are not able to deliver any information about the most significant geometrical characteristic of the clinch point, neck thickness and undercut. Furthermore, ex-situ destructive methods such as microsectioning cannot detect elastic deformations and cracks that close after unloading. In order to exceed the current limits, a new non-destructive in-situ testing method for the clinching process is necessary. This work proposes a concept to characterize clinch points in-situ by combining two complementary non-destructive methods, namely, computed tomography (CT) and ultrasonic testing. Firstly, clinch points with different geometrical characteristics are analysed experimentally using ex-situ CT to get a highly spatially resolved 3D-image of the object. In this context, highly X-ray attenuating materials enhancing the visibility of the sheet-sheet interface are investigated. Secondly, the test specimens are modelled using finite element method (FEM) and a transient dynamic analysis (TDA) is conducted to study the effect of the geometrical differences on the deformation energy and to qualify the TDA as a fast in-situ non-destructive method for characterizing clinch points at high temporal resolution.

Effect of Different Tool Geometries on the Mechanical Properties of Al-Al Clinch Joints - Ewenz, L.; Kalich, J.; Zimmermann, M.; Füssel, U. (Key Engineering Materials)
The use of clinch joints, e.g. vehicle structures, is determined by the reliability of the joint and its strength properties - in particular the fatigue strength. Clinch connections offer the advantage over form-closure and force-closure processes that they can also be used for hybrid material combinations. In order to be able to evaluate the influence of the geometry parameters such as e.g. undercut, neck thickness or also base thickness on the fatigue behavior, three clinch connections (in optimum and compromise design) with different tool parameters were designed and examined using the example of a joining task with aluminum sheet material. For this purpose, fatigue curves (F-N curves) in the range of high to very high numbers of load cycles (N = 105 to 107) were determined. In this load cycle range, a so-called "neck fracture" is mainly to be expected as the type of failure, whereas for quasi-static tests, a “buckling” is more likely to occur. The tests were carried out on single-cut overlapping shear tensile specimens. Metallographic and scanning electron microscopic examinations of the joints and the fracture surfaces served to identify the crack initiation site and to clarify the respective type of failure. Significant differences in the damage behaviour of the three clinching variants could be shown. This observation enables one step into the direction of fully understanding the relationship along the causal chain "joint requirements - joining process - fatigue strength". Thus the adaptability of the clinching process can be improved.

Modelling of thermally supported clinching of fibre-reinforced thermoplastics: Approaches on mesoscale considering large deformations and fibre failure - Gröger, B.; Hornig, A.; Hoog, A.; Gude, M. (ESAFORM 2021 - 24th International Conference on Material Forming)
Thermally supported clinching (Hotclinch) is a novel promising process to join dissimilar materials. Here, metal and fibre-reinforced thermoplastics (FRTP) are used within this single step joining process and without the usage of auxiliary parts like screws or rivets. For this purpose, heat is applied to improve the formability of the reinforced thermoplastic. This enables joining of the materials using conventional clinching-tools. Focus of this work is the modelling on mesoscopic scale for the numerical simulation of this process. The FTRP-model takes the material behaviour both of matrix and the fabric reinforced organo-sheet under process temperatures into account. For describing the experimentally observed phenomena such as large deformations, fibre failure and the interactions between matrix and fibres as well as between fibres themselves, the usage of conventional, purely Lagrangian based FEM methods is limited. Therefore, the combination of contact-models with advanced modelling approaches like Arbitrary-Lagrangian-Eulerian (ALE), Coupled-Eulerian-Lagrangian (CEL) and Smooth-ParticleHydrodynamics (SPH) for the numerical simulation of the clinching process are employed. The different approaches are compared with regard to simulation feasibility, robustness and results accuracy. It is shown, that the CEL approach represents the most promising approach to describe the clinching process.

Development of a novel adaptive joining technology employing friction-spun joint connectors (FSJC) - Wiens, E.; Wischer, C.; Homberg, W. (ESAFORM)
Joints are an essential part of modern (lightweight) structures in a broad variety of applications. The reason for this is the rapidly increasing number of different material combinations needing to be joined in application areas like the automotive industry. It is currently common to use numerous auxiliary or standardized elements instead of individually adapted joining elements. This leads to a large number of different joining elements per product and thus to high costs. An innovative approach to overcoming this issue is the design, manufacture and setting of joint-specific joining elements. A good candidate for the manufacture of adapted joining elements of this type is the so-called friction spinning process. The joining elements formed in this way can be specifically adapted to the application in question in terms of both shape and mechanical properties. The part geometry required for the properties of a given joint is formed using a universal forming tool. This makes it possible to form a wide variety of sub geometries for the auxiliary joining part as a function of the prevailing joint condition, using a single forming tool and starting from the same semi-finished bar material. By applying different process strategies for the rotational speed and feed rate during the forming operation, the same part geometry can even be given different local mechanical properties. The following contribution presents the results of ongoing research work and includes the process concept, process properties, tooling and the results of experimental investigations into the joining of two sheet metal parts with help of this new joining process.

A First Approach for the Treatment of Galvanic Corrosion and of Load-Bearing Capacity of Clinched Joints - Harzheim, S.; Steinfelder, C.; Wallmersperger, T.; Brosius, A. (Key Engineering Materials)
Corrosion is a major cause for the failure of metallic components in various branches of the industry. Depending on the corrosion severity, the time until failure of the component varies. On the contrary, a study has shown that certain riveted metal joints, exposed to a short period of mechanical loading and corrosion, have greater fatigue limits. This study gives rise to the question how different corrosion exposure times affect joint metallic components. In the present research, a theoretical approach is developed in order to evaluate the influence of galvanic corrosion on joint integrity of clinched metal joints. At first, the framework for modeling galvanic corrosion is introduced. Furthermore, a simulative investigation of a clinching point is carried out based on the assumption that corrosion leads to a reduction of the contact area which leads to a local increase in contact pressure. For this purpose, the stiffness values of individual elements in a finite element model are reduced locally in the contact area of the undercut and the contact stress along a path is evaluated. Summarizing, a modeling approach is introduced to investigate corrosion effects on load-bearing behavior of clinched joints.